The implementation of green building in Malaysia construction industry : determination of key success factors / Nor Suzila Lop, Asmalia Che Ahmad and Nik Aqlima Diyana Nik Zulkipli - Nor Suzila, Lop; Asmalia Che, Ahmad; Nik Aqlima Diyana, Nik Zulkipli (Universiti Teknologi MARA, Perak, 2016)
Green building has become increasingly on demand and important in Malaysia, however, still has not become the interest of all groups in the construction industry. Practically, green buildings should be designed and operated to reduce the overall impact of the built environment on its surroundings. Therefore the objectives of this research is to determine the key success factors of the green building implementation in Malaysia from the architect’s perception. In order to achieve the objectives of the study, a comprehensive review of literatures and questionnaire survey were carried out. The architect was chosen as the respondents to gather relevant data and information for this research. The data was analysed and the results concluded that providing education and training to construction practitioners on green building concept and technology, increase clients awareness and government initiatives to enhance g and implementation on the green building construction are the key success factors to increase the implementation and involvement of Green Building amongst the architects